Adherence to the Mediterranean Dietary Pattern and Common Mental Disorders in elderly living in São Paulo-SP-Brazil: population-based study - Bastos, Amália Almeida (2019)
Introduction: The presence of Common Mental Disorders (CMD) becomes more common with advancing age. The literature shows the beneficial effects of the Mediterranean Diet on the mental health of the elderly, but few studies have been conducted in Western countries. In addition, studies conducted in non-Mediterranean regions generally do not take into account the peculiarities of food, which do not always meet all the Mediterranean characteristics. Objective: (i) to describe the adherence to the Mediterranean dietary pattern, considering two points of view: including only foods characteristic of the original standard Mediterranean diet and including foods with non-Mediterranean characteristics (ii) to verify the association between the adherence to the two Mediterranean Dietary Patterns (MDP) and CMD in the elderly. Methods: cross-sectional population-based study; Data from the 2015 Health Survey of São Paulo were used. The presence of CMD was identified through the Self Reporting Questionnaire-20. The MDP was constructed using the Mediterranean Diet Score (calculated from data from two 24-hour dietary recall), considering two points of view: Mediterranean pattern origin-like (MPOL), which included only foods from the original Mediterranean diet; Mediterranean pattern including foods with non-Mediterranean characteristics (MPNM), which included foods submitted to procedures that diverge from the original dietary pattern. The other variables were identified through a previously structured questionnaire. The association between TMC and adherence to MPOL and MPNM was investigated through logistic regression models. The covariates for the adjustment were selected for biological plausibility. A significance level of 5% (p <0.05) was considered for final statistical tests. All data analyses were performed using Stata software (version 14). To accomplish the objectives of the present research, two manuscripts were elaborated. The aims of the 1st manuscript were: (i) describe the degree of adherence to this dietary pattern by elders from São Paulo-SP-Brazil; (ii) to identify modifications made in the form of intake of the different components of the original MDP, investigating associations with demographic and socioeconomic variables. The aims of the 2nd manuscript were: (i) To evaluate the association between the adherence to the MDP with the presence of mental disorders in these elders; (ii) To investigate these associations taking into account the two different points of view of MDP. Results: The 1st manuscript showed a moderate adherence to the two views of MDP. The greater adherence to the two proposed dietary patterns was characterized by higher intakes of vegetables, fruits, nuts, cereals, legumes and greater proportion between monounsaturated and saturated lipids and, as well as lower consumption of meat and dairy products. MPOL and MPNM were associated with formal education and age, respectively. From the 2nd manuscript, we identified that moderate and high adherence to MPOL, compared to low adherence, was associated with a lower prevalence of CMD, after adjustment for gender, age, body mass index, number of chronic diseases, per capita household income, physical activity and smoking status. The presence of CMD was not associated with MPNM adherence. Additionally, the presence of CMD was different between gender, physical activity and number of referred chronic diseases. Main conclusions (from the two manuscripts): the protective effect of MDP on CMD in elderly was observed only when the particularities of this diet were fulfilled. Other factors, associated to lifestyle, showed to be important to improve the associations with CMD. The results support the importance of programs that encourage the maintenance of healthy eating habits among the elderly.